Culture of equine bone marrow mononuclear fraction and adipose tissue-derived stromal vascular fraction cells in different media - Ribeiro,Gesiane (2013)
The objective of this study was to evaluate the culture of equine bone marrow mononuclear fraction and adipose tissue - derived stromal vascular fraction cells in two different cell culture media. Five adult horses were submitted to bone marrow aspiration from the sternum, and then from the adipose tissue of the gluteal region near the base of the tail. Mononuclear fraction and stromal vascular fraction were isolated from the samples and cultivated in DMEM medium supplemented with 10% fetal bovine serum or in AIM-V medium. The cultures were observed once a week with an inverted microscope, to perform a qualitative analysis of the morphology of the cells as well as the general appearance of the cell culture. Colony-forming units (CFU) were counted on days 5, 15 and 25 of cell culture. During the first week of culture, differences were observed between the samples from the same source maintained in different culture media. The number of colonies was significantly higher in samples of bone marrow in relation to samples of adipose tissue.